Extreme rainfall and its impacts in the Brazilian Minas Gerais state in January 2020: Can we blame climate change?. Issue 1 (14th August 2021) - Dalagnol, Ricardo; Gramcianinov, Carolina B.; Crespo, Natália Machado; Luiz, Rafael; Chiquetto, Julio Barboza; Marques, Márcia T. A.; Neto, Giovanni Dolif; de Abreu, Rafael C.; Li, Sihan; Lott, Fraser C.; Anderson, Liana O.; Sparrow, Sarah
Abstract: In January 2020, an extreme precipitation event occurred over southeast Brazil, with the epicentre in Minas Gerais state. Although extreme rainfall frequently occurs in this region during the wet season, this event led to the death of 56 people, drove thousands of residents into homelessness, and incurred millions of Brazilian Reais (BRL) in financial loss through the cascading effects of flooding and landslides. The main question that arises is: To what extent can we blame climate change? With this question in mind, our aim was to assess the socioeconomic impacts of this event and whether and how much of it can be attributed to human‐induced climate change. Our findings suggest that human‐induced climate change made this event >70% more likely to occur. We estimate that >90, 000 people became temporarily homeless, and at least BRL 1.3 billion (USD 240 million) was lost in public and private sectors, of which 41% can be attributed to human‐induced climate change. This assessment brings new insights about the necessity and urgency of taking action on climate change, because it is already effectively impacting our society in the southeast Brazil region. Despite its dreadful impacts on society, an event with this magnitude was assessed to be quite common (return period of ∼ $\sim$ 4 years). This calls for immediate improvements on strategic planning focused on mitigation and adaptation. Public management and policies must evolve from the disaster response modus operandi in order to prevent future disasters.